STRATEGIES FOR INCENTIVIZING ENTERPRISES THROUGH TAXATION IN THE CONTEXT OF THE DIGITAL ECONOMY - Abduraimova Nigora Abdugapparovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the modern global economy, the role of taxation as a strategic instrument for stimulating enterprise development is becoming increasingly important. This article examines strategies for incentivizing enterprises through taxation in the context of the digital economy. The study analyzes the impact of tax incentives on innovation, investment activity, and business competitiveness, with a particular focus on digital transformation processes. Special attention is given to mechanisms such as R&D tax credits, reduced tax rates, tax holidays, and digital tax administration systems. The findings indicate that well-designed tax policies contribute to the growth of digital enterprises, improvement of productivity, and expansion of digital markets. The article also highlights the importance of policy stability, transparency, and international cooperation in enhancing the effectiveness of tax incentives.